Aptitude measurement: is measurement validity compromised in the morning - Sideridis, Georgios; Jaffari, Fathima (Frontiers in Psychology, 2023)
The purpose of the present study was to evaluate the reliability and validity of the General Aptitude Test (GAT), a national instrument for the measurement of aptitude/achievement in the Kingdom of Saudi Arabia as a function of daytime testing. Participants were 722 students who took on the GAT across morning and evening administrations in a within-person pre-post design. Participants were matched for gender, parental education, and test center characteristics (i.e., size). The GAT was tested for its psychometric properties and its measurement invariance across time of day. Results pointed to a significant misfit using an exact invariance protocol. Specifically, there was a large number of non-invariant items pointing to Differential Item Functioning (DIF). Second, internal consistency reliabilities were consistently lower during morning testing compared to evening testing as evidenced using both statistical and visual means. Concerns about dimensionality were also raised for the morning compared to the evening administration. Last, comparison of performance levels indicated that morning testing was associated with significant decrements in performance across all domains compared to performance levels during evening testing. The results have implications for the validity of measurement and public testing policy if test validity during morning administration is compromised.